2018
DOI: 10.1080/09540121.2018.1503636
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing value and lowering costs of care: a qualitative exploration of a randomized linkage to care intervention in South Africa

Abstract: While interventions to improve HIV linkage and retention in care exist, none have demonstrated results sufficient to reach UNAIDS 90-90-90 goals. We explored values and costs of seeking clinical care through testing three strategies to improve linkage to care: Point of care CD4 testing alone (POC-CD4), POC-CD4 combined with transportation support and combined with care facilitation. We conducted in-depth interviews with participants and transcribed audio-recordings of care facilitation sessions. Participants d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The main motivation was receiving immediate treatment due to the elimination of loss or delay of results. This study corroborates findings of POC CD4 testing in South Africa and Zimbabwe where patients appreciated receiving rapid results for quicker clinical decision-making [30,31]. Numerous studies in African cohorts [12,[32][33][34][35] have described poor rates of linkage to care for those eligible for ART due to several attrition challenges in the continuum of care pathway [22,36], including the unavailability of a CD4 test result [22,37].…”
Section: Discussionsupporting
confidence: 81%
“…The main motivation was receiving immediate treatment due to the elimination of loss or delay of results. This study corroborates findings of POC CD4 testing in South Africa and Zimbabwe where patients appreciated receiving rapid results for quicker clinical decision-making [30,31]. Numerous studies in African cohorts [12,[32][33][34][35] have described poor rates of linkage to care for those eligible for ART due to several attrition challenges in the continuum of care pathway [22,36], including the unavailability of a CD4 test result [22,37].…”
Section: Discussionsupporting
confidence: 81%
“…"We knew that when we go for bloods I would come back [home] knowing what is happening with my life and … that would encourage us to take medication on time" (POC female client, [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Meaning Of Resultsmentioning
confidence: 99%
“…The emergence of patient selfregulation through the monitoring of blood test results has been described elsewhere as a 'disciplinary technology', where blood results are used to monitor patients' adherence to treatment and as 'gatekeepers' to extended benefits such as CCMDD for those adhering well [28,29]. Studies of POC CD4 testing in Zimbabwe and South Africa found that clients appreciated receiving quicker results which improved their understanding of CD4 counts [16,30] and also motivated behavior change [30].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies from South Africa reported qualitative results from multiple interventions. One evaluating integrated POC CD4 cell count testing, transport support and care facilitation reported improved psychosocial support from care facilitation that promoted engagement in care [85]. However, though transport cost reimbursement was appreciated by many participants, it was not the only means for managing transport costs for those who could either walk to the clinic or borrow money to pay for transport.…”
Section: Qualitative Values and Preferencesmentioning
confidence: 99%